Irritability‐related neural responses to frustrative nonreward in adolescents with trauma histories: A preliminary investigation. Issue 6 (22nd July 2021) - Hodgdon, Elizabeth A.; Yu, Qiongru; Kryza‐Lacombe, Maria; Liuzzi, Michael T.; Aspe, Gabriela Ibarra; Menacho, Valeria Cordeiro; Bozzetto, Lauren; Dougherty, Lea; Wiggins, Jillian Lee
Abstract: Irritability, conceptualized as a lowered frustration response threshold to blocked goal attainment (i.e., frustrative nonreward), is a common, detrimental symptom in adolescence. Yet, neural mechanisms of irritability are not well understood. This preliminary study aims to identify irritability‐related neural patterns using a novel frustrative nonreward paradigm. Our study used a diverse sample of N = 31 non‐White adolescent participants (mean age 14.53 years, SD = 1.74; 83.87% Hispanic/Latinx) to improve generalizability. During fMRI acquisition, participants performed a child‐friendly monetary incentive delay task, modified to provide incorrect, negative feedback on performance. Irritability was associated with alterations in amygdala connectivity with basal ganglia, prefrontal, temporal, and parietal regions, and in activation of prefrontal and posterior cortical structures. Across clusters, youths with greater irritability showed activation/connectivity differences between reward blocked versus received conditions in the opposite direction compared to youths with lowered irritability. Alterations in amygdala‐temporoparietal connectivity and lingual gyrus activation demonstrated an altered irritability‐related recovery effect from the previous trial. These findings support the central role of frustrative nonreward as a key irritability pathway. Our work is one of the first to document neural correlates of difficult recovery from frustration characteristic of irritability and provides insight into novel treatment targets for irritability in diverse populations.